Cartagena: New Urban Focus of Visceral Leishmaniasis in Colombia. (2016)
In Colombia, Visceral Leishmaniasis (VL) is predominant in rural areas of the Caribbean and MagdalenaRiver Valley regions. A one year old female inhabitant of an urban zone in the city of Cartagena displayed symptoms of hepato/splenomegaly, anemia, leucopenia and malnutrition. She had not visited endemic areas for VL but tested positive for VL serologically. After treatment with Glucantimer, her symptoms disappeared, however, three months later, her Montenegro test came out positive. To identify the presence of VL vectors and reservoirs, and also environmental conditions suitable for VL transmission in the area of the reported VL case. There were carried out epidemiological, clinical, immunological and molecular studies to look for other people infected with VL. Also it was searched for VL reservoirs and vectors in the area. The study area presented environmental conditions suitable for VL transmission. No infected children were found, but seven adults had positive Montenegro tests, suggesting exposure to the parasite in this area. Additionally, the VL vector species Lu. evansi was found inside some of these people’s homes. Finally, a domestic dog and a D. marsupialis individual were also found to be infected with Leishmania infantum, confirmed by laboratory. It was demonstrated the presence of a new urban VL scenario in Colombia, which should be object of public health surveillance and acts in the studied area.